Multilevel Analysis: Village Does Not Have Contextual Effect on Hepatitis A Outbreak in Pacitan, East Java, Indonesia - Sugeng Retyono; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Hepatitis A virus infection (HAV) has generated about half of the total infection of hepatitis in the world. Poor envi